Exciton-polaritons in 2D dichalcogenide layers placed in a planar microcavity: tuneable interaction between two Bose-Einstein condensates - Vasilevskiy, Mikhail (2015)
Exciton-polariton modes arising from interaction between bound excitons in monolayer thin semiconductor sheets and photons in a Fabry-Perot microcavity are considered theoretically.We calculate the dispersion curves, mode lifetimes, Rabi splitting, and Hopfield coefficients of these structures for two nearly 2D semiconductor materials, MoS2 and WS2, and suggest that they are interesting for studying the rich physics associated with the Bose-Einstein condensation of exciton polaritons. The large exciton binding energy and dipole allowed exciton transitions, in addition to the relatively easily controllable distance between the semiconductor sheets, are the advantages of this system in comparison with traditional GaAs or CdTe based semiconductor microcavities. In particular, in order to mimic the rich physical properties of the quantum degenerate mixture of two bosonic species of dilute atomic gases with tunable interspecies interaction, we put forward a structure containing two semiconductor sheets separated by some atomic-scale distance (l) using a nearly 2D dielectric (e.g., h-BN), which offers the possibility of tuning the interaction between two exciton-polariton Bose-Enstein condensates. We show that thedynamics of this structure are ruled by two coupled Gross-Pitaevskii equations with the coupling parameter∼ l−1.